2007
DOI: 10.1002/gcc.20428
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom pattern of chromosome aberrations in 17β‐estradiol‐induced rat mammary tumors: Indications of distinct pathways for tumor development

Abstract: Estrogens play an important role in breast cancer etiology and the ACI rat provides a novel animal model for defining the mechanisms through which estrogens contribute to mammary cancer development. In crossing experiments between the susceptible ACI strain and two resistant strains, COP (Copenhagen) and BN (Brown Norway), several quantitative trait loci (QTL) that affect development of 17beta-estradiol (E2)-induced mammary tumors have been defined. Using comparative genomic hybridization (CGH), we have analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
(67 reference statements)
2
14
0
1
Order By: Relevance
“…Our previous study of E 2 -induced rat mammary carcinomas using chromosomal CGH revealed a clear pattern of nonrandom chromosomal involvement (32). Furthermore, mammary cancers induced in rats by the heterocyclic amine 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine exhibited discernable somatic abnormalities (33) although distinct from chromosomal copy number changes observed in the estrogeninduced mammary tumors (32). These studies, including our present, suggest that distinct pathways may act in a carcinogen/ estrogen-specific manner and contribute to tumor development.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our previous study of E 2 -induced rat mammary carcinomas using chromosomal CGH revealed a clear pattern of nonrandom chromosomal involvement (32). Furthermore, mammary cancers induced in rats by the heterocyclic amine 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine exhibited discernable somatic abnormalities (33) although distinct from chromosomal copy number changes observed in the estrogeninduced mammary tumors (32). These studies, including our present, suggest that distinct pathways may act in a carcinogen/ estrogen-specific manner and contribute to tumor development.…”
Section: Discussionmentioning
confidence: 92%
“…Thus far, only a limited number of studies have reported DNA copy number profiles of rat mammary carcinomas. Our previous study of E 2 -induced rat mammary carcinomas using chromosomal CGH revealed a clear pattern of nonrandom chromosomal involvement (32). Furthermore, mammary cancers induced in rats by the heterocyclic amine 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine exhibited discernable somatic abnormalities (33) although distinct from chromosomal copy number changes observed in the estrogeninduced mammary tumors (32).…”
Section: Discussionmentioning
confidence: 95%
“…Since proposed, tree models have been used by many researchers to explore the molecular mechanism of tumor development, including the CGH data from renal cell carcinoma [20,22] , hereditary breast cancers [23] , bladder cancer [24] , head and neck squamous cell cancer [25] , nasopharyngeal carcinoma [14,26] , thymoma [27] , and rat mammary tumors [28] , and breakpoint data from ovarian cancer [21] . These models have been used to identify early events, as well as marker events of subtypes of tumors, defining the sequence of these events and the involved pathways.…”
Section: Oncogenetic Tree Modelsmentioning
confidence: 99%
“…Concurrent treatment with tamoxifen dramatically diminishes the ability of E2 to induce mammary cancer in ACI rats, indicating an important role of ER mediated pathways in mammary tumorigenesis (Li, et al 2002; Singh, et al 2011). The mammary cancers that develop in E2 treated ACI rats express ERα and progesterone receptor (Pgr), are dependent upon estrogens for survival and growth, and exhibit non-random patterns of chromosome copy number alterations that mirror somatic copy number alterations frequently observed in breast cancers (Adamovic, et al 2007; Harvell, et al 2000; Ruhlen, et al 2009). Together, these data illustrate multiple important similarities between the mammary cancers induced by E2 in ACI rats and luminal type breast cancers in humans.…”
Section: Introductionmentioning
confidence: 99%